Association Between Parenting Styles And Adolescents’ Mental Disorders: Findings Among Pre-university Students - Siti Roshaidai Mohd Arifin; Nur Syila Syahida Syaziman; Khadijah Hasanah Abang Abdullah; Karimah Hanim Abd Aziz; Khairi Che Mat; Noor Azimah Muhammad; Shanti Wardaningsih (Penerbit Universiti Sains Malaysia, 2024)
Indexed by Scopus